Estrategias de marketing digital en el Almacén Don Pato “Jr.” Ubicado en la ciudad de Babahoyo en el año 2023. - Vera Aguilar, Estefany Gabriela (2024)
Applying digital marketing strategies in companies is essential for growth and relevance in today's business environment. Consumer trends are forcing brands to use digital approaches to reach and captivate audiences. Effective implementation of digital marketing strategies promotes sustainable business growth. The company Don Pato “Jr” is a recognized company in the city of Babahoyo. This case study aims to find an online presence to have a connection with your customers and expand your digital capabilities. Don Pato “Jr” has demonstrated a lasting commitment to excellence with the quality of its products and services. However, in today's digital environment, the adoption of digital marketing and strategies is presented as an essential catalyst to maintain and improve its position. competitive. The importance of implementing a digital marketing and strategy is highlighted as a method for the company, since every time people, especially young people, understand the importance of digitizing markets, by allowing them to make purchases from wherever they are through computers or mobile devices, digital marketing has become become the key to knowing and satisfying the needs of users and potential clients. Therefore, it continues to advance to become a central aspect of business today and in the future.